The Oxford Handbook of Religion, Conflict, and Peacebuilding - Omer, Atalia ca. 20./21. Jh. (Oxford Handbooks Ser., 2015)
The book provides a comprehensive overview of the literature on religion, conflict, and peacebuilding. With a focus on structural and cultural violence, the volume also offers a cutting edge interdisciplinary reframing of the scope of scholarship in the field.